A comparison of the role of aggression in the association between hostile interpretation bias and antisocial personality features between young offenders and university students. (7th February 2023) - Lai, Lizu; Cai, Manqi; Zou, Cailing; Zhao, Ziyi; Zhang, Lin; Ren, Zhihong
Abstract: Background: Antisocial personality features in adolescents are frequently associated with delinquency and constitute the problem that most concerns the criminal justice system and the public. Hostile interpretation bias has been identified as a candidate for explaining emergent adolescent antisocial personality problems and aggression, but it is unclear whether offenders and non‐offenders show differences in the relationships between hostile interpretation bias, aggression and antisocial personality features. Aims: To compare relationships between hostile interpretation bias and a personality measure between incarcerated teenagers and first year university students and to explore aggression and criminal history as mediating or moderating variables. Methods: Fifty‐three 16–18‐year‐old incarcerated male offenders and 69 17–20‐year‐old male university students were recruited, the former through institutional staff and the latter by online advert only. Individuals in both groups self‐rated, in private, on the Word and Sentence Association Paradigm‐hostile (WSAP), The Ambiguous Intentions Hostility Questionnaire (AIHQ), Hostility Interpretation Bias Task (HIBT) as tests for hostile interpretation bias, and on the Buss‐Perry Aggression Questionnaire and on Hyler's Personality Disorder Questionnaire (PDQ‐4). Among the students, criminal history was assessed by a self‐reported binary question. LASSO regressions were used to test inter‐relationships between hostile interpretation bias and aggression or antisocial personality traits. Mediation and moderation were tested using MPLUS 7.4. Results: The WSAP and AIHQ, as measures of self‐reported hostility bias, had relationships with self‐reported aggression (Pearson r 0.24–0.58, p  < 0.001) and with antisocial personality features ( r 0.36–0.50, p  < 0.001), the HIBT did not. Aggression scores mediated the relationship between hostile interpretation bias and antisocial personality features. Furthermore, the relationship between hostile interpretation bias and aggression was stronger among the young offenders (estimates 0.43–0.75) than among the university students without criminal history (estimates 0.13–0.36). Conclusions: Hostile interpretation bias appears to promote antisocial personality features by increasing an individual's aggression, regardless of social status, although the effect was much stronger among the young offenders. To reduce young people's antisocial personality features, future studies should perhaps focus on evaluating strategies to reduce hostile bias or prevent it from being expressed in aggressive behaviours.